Post-traumatic stress disorder and its associated factors among internally displaced people due to conflict in Northwest Ethiopia - Melkam, Mamaru; Medfu Takelle, Girmaw; Kibralew, Getasew; Nakie, Girum (Frontiers in Public Health, 2025)
BackgroundPost-traumatic stress disorder (PTSD) is a mental health condition that develops after being exposed to trauma, such as experiencing or witnessing life-threatening events, including war and other natural disasters. Despite the high levels of conflict, little attention has been given to post-traumatic stress disorder, particularly in low- and middle-income countries. Therefore, this study aimed to determine the prevalence of post-traumatic stress disorder and its associated factors among internally displaced people in Northwest Ethiopia.MethodsA cross-sectional study design was employed from June to July 2022 in Northwest Ethiopia among internally displaced people. Simple random sampling was used to recruit 410 study participants. The standard tools used in this study included the Post-Traumatic Stress Disorder Checklist for DSM-5 (PLC-5), Kessler-10, and Oslo Social Support Scale to assess various variables. Binary logistic regression analysis was used to identify factors associated with post-traumatic stress disorder. Statistically significant factors were selected at a 95% confidence interval (CI) with adjusted odds ratio (AOR).ResultsThe prevalence of post-traumatic stress disorder among internally displaced people was 54.3%, with a 95% CI (49.5, 59.3). Current substance use [AOR 95% CI: 2.01(1.16, 3.48)]; living arrangements, such as living alone or with non-relatives [AOR = 2.13; 95% CI (1.17, 3.86) and AOR = 2.39; 95% CI: (1.21, 4. 70), respectively]; being violated [AOR = 2.49; 95% CI: (1.26, 4.94)]; and psychological distress [AOR = 3.21; 95% CI: (4.35, 9.34)] were significantly associated with post-traumatic stress disorder.ConclusionThe prevalence of post-traumatic stress disorder among internally displaced people was high. Therefore, stakeholders should provide immediate interventions that include further assessments using diagnostic criteria. In addition, Eye Movement Desensitization and Reprocessing psychotherapy along with selective serotonin reuptake inhibitors as psycho-pharmacological treatment are recommended. Furthermore, efforts should be made to reduce the identified risk factors to improve outcomes for individuals with post-traumatic stress disorder.